A retrospective study on periparturient disorders in crossbred cows at organized farms in Uttar Pradesh - SINGH, RAJEEV; SHANKAR, HARRI; ARORA, B M (The Indian Journal of Animal Reproduction, 2023)
The prevalence of dystokia, stillbirths, abortions, retention of foetal membranes, prolapse of uterus and metritis were ascertained at organized farms of Bareilly and Allahabad Districts of Uttar Pradesh, during the period September I st, I 995 to August 3 I, 1999. The prevalence of dystokia, stillbirths, abortions, retention of foetal membranes, prolapse of uterus and metritis were 0.84, 4.60, 3.68, 15.22, 0.92 and 18.14 per cent respectively at Bareilly and 4.86, 5.24, 4.61 , 23.32, 2.12 and 33.42 per cent respectively, at Allahabad. The highest pre\’alence of dystokia, abortions, retention of foetal membranes were observed in summer season (1.41, 4.58, 18.66 and 6.42, 9.63, 32.09 per cent) and still births in rainy season (9.72 and 7.41 per cent) at both farms of Bareilly and Allahabad, respectively. The metritis was common in rainy season at Bareilly (23 .96) and summer (42.25) at Allahabad.